2017
DOI: 10.22158/jbtp.v5n1p9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Saudi Corporate Companies Online Recruitment

Abstract: Organisations are already using their corporate website to advertise jobs and receive resumes online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In spite of this, based on previous research conducted by (Landers and Schmidt, 2016;McDonald and Thompson, 2016), Hooley (2017) posits that organizations as employers are making considerable use of the internet for the purpose of talent attraction in the recruitment and screening of potential job applicants. Furthermore, a thorough scrutinization of the top ten Forbes listed Saudi corporate websites by Khan (2017) revealed that potential talents were attracted by organizations having attractive corporate and career websites. Likewise, commercial banks are making use of career websites to portray the banks' specific employer image such that an online search of banks' career websites disclose unique arrangement of information targeted at the talent market (Amine et al, 2013).…”
Section: Career Websitesmentioning
confidence: 99%
“…In spite of this, based on previous research conducted by (Landers and Schmidt, 2016;McDonald and Thompson, 2016), Hooley (2017) posits that organizations as employers are making considerable use of the internet for the purpose of talent attraction in the recruitment and screening of potential job applicants. Furthermore, a thorough scrutinization of the top ten Forbes listed Saudi corporate websites by Khan (2017) revealed that potential talents were attracted by organizations having attractive corporate and career websites. Likewise, commercial banks are making use of career websites to portray the banks' specific employer image such that an online search of banks' career websites disclose unique arrangement of information targeted at the talent market (Amine et al, 2013).…”
Section: Career Websitesmentioning
confidence: 99%